Estudos para implantação de sistema de reúso dos efluentes provenientes de equipamentos destiladores e condensadores - Marisco, Lenisa Veiga (2007)
In the current world, the care with the resources you renewed and you didn t renew comes gradual acquiring an importance each bigger time inside of the organizations, as much the governmental one as not-governmental ones. The major factors are the concern to the cause and consequence of environmental damage. Water is an element of extreme need for the lives of human beings, thus it is extremely important to control their waste through actions aimed at awareness of the users. The large increase in demand of water, caused by population growth and productive activities arising, plus the growing degradation of water bodies, create a scenario of shortage of water resources increasingly common in several regions. The need to promote the growth of the supply of water is very important as you experience the growth of demand for this input in urban areas. Creating the need for implementation of programmes to make rational use of water with consequent conservation of water resources. By using water for reuse, and certain uses and with favourable conditions, works up the development of sustainable supply systems, where the relationship between supply and demand is fully addressed. We need the encouragement to actions which identify, evaluate and improve the performance of equipment that use large amounts of water such as capacitors, distillers and cleanser while generating effluent quality with allowing its use in activities that do not require water drinking. In that sense, this work is to identify such equipment in the laboratories of I Campus of the University of Passo Fundo, to study its principle of operation and in particular its demands for water and the volumes of waste generated, as well as identify the quality of this effluent to the proposition of programmes for the conservation of water surrounding the reuse or reuse the effluent. The results demonstrated that such equipment consume a large volume of clean water and descartam a considerable amount of effluent quality with allowing its reuse in their facilities of the laboratories, which are installed. For this we need the optimization of the processes involving the use of waste water and correction, reducing the demand for potable water and the release of effluents